Effectiveness of Guided Discovery Learning-Based E-LKPD During the Covid-19 Pandemic to Improve Student Learning Outcomes - Loly - Suwandani; Emmawaty Sofya; Tasfiri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
This study aims to describe the improvement of student learning outcomes through learning using E-LKPD based on guided discovery learning during the Covid-19 pandemic. The population in this study were all students of class XI MIPA at SMA Negeri 13 Bandar Lampung for the academic year 2021/2022. The sample in this study is class XI MIPA 2 as the control class and XI MIPA 4 as the experimental class taken using random sampling technique. The research method used is a quasi-experimental with pretest-posttest control group design. The data analysis technique of student learning outcomes uses the t-test on the n-Gain value of students. Learning outcomes data were processed using Microsoft Office Excel 2019 software and analyzed using SPSS software version 25.0 for Windows. Based on the results of the t-test obtained the value of sig. (2-tailed) 0.000 with H0 rejection test criteria if the sig value 0.05. Therefore, in this study, accept H1 which means that the average learning outcomes of students who use E-LKPD based on guided discovery learning in the experimental class are greater than the control class. The results of the effect size test obtained a value of 0.79 with the criteria of “large”. Based on the results of data analysis, it can be concluded that learning using E-LKPD based on guided discovery learning is effective in improving student learning outcomes with great influence.